PENGGUNAAN MEDIA POHON LITERASI PADA KETERAMPILAN MEMBACA SISWA KELAS III SD NEGERI 202 GRESIK - Zahrotul Faizza; Lita Aditya Khoirun Nisa; Noviardani Kartika Prameswari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education is an important part of human life, which can only happen when teachers and students communicate directly. The ability to read words and phrases is the main focus of reading skills. Tools or learning resources that support literacy activities are called literacy tree media. It takes the form of a visual tree. This study uses a qualitative descriptive methodology. Ten third-grade students at UPT SD Negeri 202 Gresik became the data and research sources. The approaches used to collect data in this study were: (1) observation, (2) interviews, and (3) documentation. Based on the research findings regarding the impact of literacy tree media on the reading skills of third-grade students at UPT SD Negeri 202 Gresik, it can be concluded that teachers effectively utilize learning media in teaching reading to their students. To make learning more conducive and enjoyable, educators have used engaging media. Students' interest in using the literacy tree media indicates that they can read the content of short stories on the topic of Rights and Responsibilities at home clearly and fluently. Additionally, students gain strong understanding and information.